EFFECT OF ADDITION OF PROBIOTIC EM4 (EFFECTIVE MICROORGANISM) WITH DIFFERENT DOSES ON FEED AGAINST THE LENGTH AND WEIGHT RELATIONSHIP OF CARP (Cyprinus carpio) - karel, melda; Hilyana, Sitti; Lestari, Dewi Putri (Jurnal Perikanan Unram, 2020)
This research aimed to know the effect of the addition of commercial probiotics EM4 (Effective microorganism) to the length and weight relationship of carp (Cyprinus carpio). This study used a Completely Randomized Design with five treatments, namely P1 (without the addition of probiotics), P2 (probiotics 10 ml / kg of feed), P3 (probiotics 15 ml / kg of feed), P4 (probiotics 20 ml / kg of feed), P5 ( probiotics 25 ml / kg of feed) and each treatment has 3 replications so that the total experiment is 15 units. The results showed that there was a significant influence (p> 0.05) on the growth of absolute length and weight, so that further tests were carried out to determine the best treatment to produce growth in length and weight of carp, note that P3 (probiotics 15 ml / kg of feed) is the best treatment in this study.